Analisis Pergeseran Horisontal Di Bendungan Panglima Besar Soedirman - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK Deformation often cause negative impacts. It is worried that it will happen to the Panglima Besar Soedirman darn. To minimize the impacts, PLTA Mrica has conducted deformation monitoring periodically every three months. Nevertheless deformation analysis especially using geodetic approach has not been performed yet. This research tries to analyze horisontal displacement in the Panglima Besar Soedirman dam using geodetic approach based on the existing data (2002, 2003 and 2004). Data processing was performed using Least Square Adjustment method and direct method, and then the network conformity test and point displacement test was used to analyze the displacement. The result of the direct method shows the displacement of centimeter level happen at D13. Meanwhile, the result of the Least Square Adjustment method shows that all of the observed points were shifted. The displacement of meter level seems to happen at D13, however this is not realistic because methodology of measurement is not appropriate with the methodology of data processing. Keywords: Pergeseran horisontal, bendungan